POST-COVID-19HEALTHCARE:TRANSITIONTOANEW NORMAL - Rehman, Safia (Journal of Gandhara Medical and Dental Science, 2021)
The COVID-19 pandemic has challenged the health care system to face extraordinary circumstances. These challenges bring forth a new era with a certain high point like the transition to the fusion of in person and digital health practice framework. Post COVID-19 there is a lot of sludge in health care, inthe form of administrative processes and requirements that slow down the core activities of providing care. COVID-19 crisis is used as an opportunity to reduce administrative burdens which most of the times made a primary care physician feel demoralized and burned out’. The focus of healthcare has shifted from hospitals to homes using telemedicine technologies which enabled virtual visits and remote care delivery. COVID-19 signified the telemedicine to be an essential component of healthcare delivery. It proved to an effective and safe way of treatment and avoiding nosocomial infections’. Previously, telemedicine was not considered to be a normal consultation method, nowadays it’s part of the normal lives of the patients as well as health care providers. The other big advantage of this great tool is that one can consult doctors even from very remote areas, which is impossible to consult physically. Different technological advancement like Artificial Intelligence-based diagnostics, cloud-based storage of medical records and integration of information in and outside hospitals were explored and adopted in the COVID-19 pandemic. Data is the key to advance research and refine health care process and outcomes for the COVID-19 patients. The digitalization of the health care system can provide significant benefit’. The phenomenon of digitalization of healthcare system is especially benefited for the developing world, because, in the resource-limited environment, a lot of cost and resources can be saved by opting paperless systems. When people were locked down, social media was pivotal in creating awareness and educating people in a short period*. There was a lot of stuff regarding COVID-19 pandemic on social media and most interestingly it was portrayedin a way that one could not be able to neglect the content. Consequently, intentionally or unintentionally many of the users opted some of the measures for prevention of the deadlyinfection. The pandemic has shown us that countries with the more robust public health system, primary care services and a healthier population perform well in the fight against the pandemic. Safeguard of voluntary and community organization is essential’. At the same time the countries with fewer resources and with limited measures for controlling massive disasters, in the form of this pandemic, got exposed. This is an alarming situation for global organizations like the World Health Organization and other health-related global leaders to work together for making sure that health resources be equally provided to all the countries across the globe. The COVID-19 pandemic educated the underdeveloped countries regarding infection control measures like Biosafety and Biosecurity. Health official shifted their resources in maintaining hygienic measures to patients, doctors and support staff. Overall, this led to great impact in revolutionizing patient care and improving quality standards. The deficiency of trained staff in Intensive Care Unit and Accident & Emergency is also highlighted in this pandemic. Hence the focus should be on enabling the existing resources to acquire skill in these specialties. The people started making the right food choice, adapting to healthy physical exercise and ensuring therapies to relieve stress and anxiety’. The pandemic brings changes to the healthcare system, whichis not entirely new, these were introduced by technologists earlier; the system is going back to normal that is stronger, smarter and healthier. Hospitals should ensure that their infrastructure is sufficiently ready to cope with the advent of digitalization.